Comparative assessment of the effect of titanium dioxide – based nanoparticles on boar germ cells in vitro - O.P. Yavorovsky; T.S. Zazuliak; D.D. Ostapiv; V.M. Riabovol; O.V. Demetska (Medičnì Perspektivi, 2022)
Modern titanium dioxide nanomaterials, in particular modified with nanosilver, have antiviral, antibacterial, antifungal activity, cytotoxic effects in vitro experiments and can affect germ cells of warm-blooded laboratory animals. The research aims to study the effect of different types of titanium dioxide nanoparticles on the physiological and biochemical characteristics of wild boar germ cells in vitro. When applying the maximum dose (LD50) of the studied nanopowders in all samples, sperm survival was probably lower than in the control: by 41.9% (р<0.001) ‒ under the action of TiO2 nanoparticles (hereinafter NPs) (Frantsevich Institute for Problems of Materials Science of NAS of Ukraine, hereinafter IPM), by 28.0% (р<0.05) ‒ under the action of TiO2 NPs (Acros Organics), by 53.5% (р<0.001) ‒ under the action of 4% Ag-TiO2 NPs (IPM) and by 55.9% (р<0.001) ‒ are the action of NPs 8% Ag-TiO2 (IPM). Nanopowders of different based on titanium dioxide manufacturers, characterized by similar morphological characteristics and varying degrees of nanosilver addition (Ag content from 0 to 8%), starting from a dose of 1/10 LD50, can have a damaging effect on the germ cells of wild boars, which is manifested by a decrease in the respiratory activity of sperm and cytochrome oxidase activity, by increasing succinate dehydrogenase activity. The most sensitive marker was the sperm survival rate, the value of which significantly decreased under the action of 8% Ag-TiO2 nanoparticles (IPM) at a dose of 1/100 LD50, which is a consequence of disruption of the activity of mitochondrial enzymes and, accordingly, resynthesis of ATP. Our results confirm and extend the data on the nature of the damaging effect of titanium dioxide-based nanoparticles on germ cells of warm-blooded animals due to oxidative stress. The obtained experimental data will be taken into account in the hygienic regulation of the investigated nanopowders.